Radiology and Enterprise Medical Imaging Extensions (REMIX). - Erdal, Barbaros S.; Prevedello, Luciano M.; Qian, Songyue; Demirer, Mutlu; Little, Kevin; Ryu, John; O’Donnell, Thomas; White, Richard D. (Journal of Digital Imaging, 2018)
Radiology and Enterprise Medical Imaging Extensions (REMIX) is a platform originally designed to both support the medical imaging-driven clinical and clinical research operational needs of Department of Radiology of The Ohio State University Wexner Medical Center. REMIX accommodates the storage and handling of “big imaging data,” as needed for large multi-disciplinary cancer-focused programs. The evolving REMIX platform contains an array of integrated tools/software packages for the following: (1) server and storage management; (2) image reconstruction; (3) digital pathology; (4) de-identification; (5) business intelligence; (6) texture analysis; and (7) artificial intelligence. These capabilities, along with documentation and guidance, explaining how to interact with a commercial system (e.g., PACS, EHR, commercial database) that currently exists in clinical environments, are to be made freely available.